THE EFFECT OF LIFESTYLE, HALAL LABELING AND RELIGIOSITY ON STUDENTS’ COSMETIC BUYING INTEREST IN MALANG CITY - Rahma, Dinda Nuzulia; Askandar, Noor Shodiq; Taqwiem, Ahsani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to examine the influence of lifestyle, halal labeling, and religiosity on the purchase intention of cosmetics among university students in Malang City. This research uses a quantitative approach with an explanatory method. Data were collected through questionnaires distributed to 154 student respondents who use cosmetics. The analysis techniques used include validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that simultaneously, lifestyle halal labeling, and religiosity have a positive and significant effect on purchase intention. Partially, each of the three variables also has a positive and significant influence. The adjusted R square value of 49.5% indicates that purchase intention can be explained by these three variables, while the remaining percentage is influenced by other factors outside the model.